Effects of cloth face masks on physical and cognitive performance during maximal exercise testing. Issue 3 (4th May 2023) - Driver, Simon; Brown, Katelyn D.; Gilliland, Taylor; Reynolds, Megan; Bennett, Monica; McShan, Evan; Kim, Chol Ho J.; Freese, Eric; Belling, Patrick; Gottlieb, Robert L.; Jones, Alan
Abstract: Wearing a cloth face mask has been shown to impair exercise performance; it is essential to understand the impact wearing a cloth face mask may have on cognitive performance. Participants completed two maximal cardiopulmonary exercise tests on a cycle ergometer (with and without a cloth face mask) with a concurrent cognitive task. Blood pressure, heart rate, oxygen saturation, perceived exertion, shortness of breath, accuracy, and reaction time were measured at rest, during each exercise stage, and following a 4-minute recovery period. The final sample included 35 adults (age = 26.1 ± 5.8 years; 12 female/23 male). Wearing a cloth face mask was associated with significant decreases in exercise duration (−2:00 ± 3:40 min, P  = 0.003), peak measures of maximal oxygen uptake (−818.9 ± 473.3 mL/min, −19.0 ± 48 mL·min -1 ·kg -1, P  < 0.001), respiratory exchange ratio (−0.04 ± 0.08, P  = 0.005), minute ventilation (−36.9 ± 18 L/min), oxygen pulse (−3.9 ± 2.3, P  < 0.001), heart rate (−7.9 ± 12.6 bpm, P  < 0.001), oxygen saturation (−1.5 ± 2.8%, P  = 0.004), and blood lactate (−1.7 ± 2.5 mmol/L, P  < 0.001). While wearing a cloth face mask significantly impaired exercise performance during maximal exercise testing, cognitive performance was unaffected in this selected group of young, active adults.